Plasmonic sensor with high figure of merit based on differential polarization spectra of elliptical nanohole array. Issue 38 (25th September 2017) - Ai, Bin; Basnet, Pradip; Larson, Steven; Ingram, Whitney; Zhao, Yiping
Abstract : The figure of merits (FOMs) of plasmonic sensors can be pushed to a new level (∼700 RIU −1 ) based on the differential polarization transmission spectra of elliptical nanoholes. Abstract : Using the difference of the polarization transmission spectra of elliptical nanohole arrays (ENAs), the figure of merit (FOM) of the sensor performance of ENA can be significantly improved, and is inversely proportional to the measurement resolution. By optimizing the aspect ratio of the elliptical holes, Ag thickness, substrate-effect, and adhesive layer, the sensitivity, FOM, and relative sensitivity of the ENA can be improved to be 775 nm RIU −1, 705 RIU −1, and 70.23%, respectively, with an excellent linear dependence on the change of refractive index. Such a high-performance sensor also can be used in monitoring the molecule adsorption and RNA hybridization, revealing a highly localized near-field enhancement. This will benefit the sensing of surface-specific binding events in biologic detection and medical diagnosis.